Development of insurance, opportunities and practical experience in the formation of social and economic security (regional aspect) - Vyshnevska, O. (UKRAINIAN BLACK SEA REGION AGRARIAN SCIENCE, 2022)
The development of modern business, the implementation of approaches to local, regional (territorial) development encourage the activation of the spread of the insurance sector. Mechanisms for the introduction of appropriate financial levers make it possible to neutralize threats and increase the financial stability of market entities, which is proven by the experience of European states. The purpose of the study is to substantiate the essence, features and main tasks in the field of insurance, to determine the priority directions of the development of the insurance market, to coordinate the interests of the participants and effective partnership in view of the need to form prerequisites for the socio-economic stability and security of the state and its individual regions. The main task of the research is to assess the situation, existing forecasts and determine the priority directions of the development of the insurance sector, taking into account the needs of society, interests, partnership mechanisms, including at the international level. Methods of scientific knowledge were used during the research. The author has researched the essence and development possibilities of the insurance sector, taking into account the practical experience of the countries of the world and modern trends in the insurance market. The importance of the insurance sector for society, regional development and increasing opportunities in the field of investment activity has been proven. Regional features were analyzed and priority directions of development were determined, taking into account the needs of spheres and branches of the economy, territorial communities. The effect of effective interaction of insurance market participants on the possibilities of expanding insurance services is determined.The relevance of partnership in the implementation of insurance approaches and mechanisms of interaction between participants was determined. The author stipulates the need to regulate the interests of all participants, as well as mutual coordination of actions and levels of responsibility, opportunities for public-private partnership in regional development, investment activities. The need to guarantee the practical results of interaction in the field of insurance and the formation of prerequisites for social and economic security, including taking into account regional characteristics, is stipulated. The results of the author's research can be used for further research in the field of insurance, interaction of participants on the basis of partnership